Prevalence of antibiotic-resistant Cutibacterium acnes (formerly Propionibacterium acnes) isolates, a systematic review and meta-analysis - Masoumeh Beig; Omid Shirazi; Elaheh Ebrahimi; Abbas Zare Banadkouki; Narges Golab; Mohammad Sholeh (Journal of Global Antimicrobial Resistance)
Objective: This study aimed to assess the overall antibiotic susceptibility of Cutibacterium acnes (C. acnes), a bacterium implicated in acne vulgaris, with a particular focus on clindamycin and fluoroquinolones, which are commonly used in inflammatory acne treatment. Methods: A systematic search of Scopus, PubMed, Web of Science and EMBASE databases was conducted to identify relevant studies. Pooled prevalence estimates were calculated using a random-effects model, and additional analyses included quality assessment, evaluation of publication bias, meta-regression and subgroup analyses based on antimicrobial susceptibility methods and year of publication. Results: The analysis incorporated a total of 39 studies. The random-effects model revealed that the proportion of clindamycin-resistant isolates was 0.031 (95% CI: 0.014–0.071). Additionally, macrolides, including erythromycin (0.366; 95% CI: 0.302–0.434) and azithromycin (0.149; 95% CI: 0.061–0.322), exhibited distinct prevalence rates. Tetracyclines, including doxycycline (0.079; 95% CI: 0.014–0.071), tetracycline (0.062; 95% CI: 0.036–0.107) and minocycline (0.025; 95% CI: 0.012–0.051), displayed varying prevalence estimates. Fluoroquinolones, including ciprofloxacin (0.050; 95% CI: 0.017–0.140) and levofloxacin (0.061; 95% CI: 0.015–0.217), demonstrated unique prevalence rates. Additionally, the prevalence of the combination antibiotic trimethoprim/sulfamethoxazole (SXT) was estimated to be 0.087 (95% CI: 0.033–0.208). Conclusion: The study findings highlight a concerning increase in antimicrobial-resistant C. acnes with the use of antibiotics in acne treatment. The strategic utilization of appropriate antimicrobials has emerged as a crucial measure to mitigate the emergence of antimicrobial-resistant skin bacteria in acne management.